Teachers’ Perspective about National Assessment: How do Vocational Teachers Enhance Literacy in the Classroom? - Istiyono, Edi; Retnawati, Heri; Rusmaningtias, Sheptiani (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2026)
In the 21st century, students are required to incorporate literacy skills into their learning. In this context, the teacher’s role is pivotal, as they are the primary influencers in shaping the learning journey. However, information on how teachers incorporate literacy in this context is not widely available. Therefore, it is necessary to explore this aspect further. The study adopts a phenomenological research approach in which data is collected through in-depth interviews, and thematic analysis is performed using manual methods and ATLAS.ti 23. The research findings reveal that some teachers are familiar with the National Assessment, which primarily focuses on literacy assessment and does not mention character development. Most teachers perceive the National Assessment as a tool to enhance the quality of education. Preparing for the National Assessment involves focusing on classroom learning and infrastructure, particularly computers and networks. The final theme highlights the unique experiences of each vocational teacher in teaching literacy in their schools. Participants shared their perspectives in various ways, most of which incorporated data into the learning process. They believe that this approach can significantly enhance students' literacy. Our research also revealed several recommendations based on the teachers’ perspectives on science subjects.